2014
DOI: 10.1016/j.molonc.2014.03.005
|View full text |Cite
|
Sign up to set email alerts
|

Targeted pancreatic cancer therapy with the small molecule drug conjugate SW IV‐134

Abstract: Pancreatic adenocarcinoma is highly resistant to conventional therapeutics and has been shown to evade apoptosis by deregulation of the X-linked and cellular inhibitors of apoptosis proteins (XIAP and cIAP). Second mitochondria-derived activator of caspases (Smac) induces and amplifies cell death by reversing the anti-apoptotic activity of IAPs. Thus, Smac-derived peptide analogues (peptidomimetics) have been developed and shown to represent promising cancer therapeutics. Sigma-2 receptors are overexpressed in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
37
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 37 publications
1
37
0
Order By: Relevance
“…[1618] Multiple classes of sigma-2 ligands have been pharmacologically characterized as either agonists, partial agonists or antagonists. [1921] Sigma-2 agonists have been shown to undergo receptor-mediated endocytosis providing a method to deliver therapeutics into cancer cells.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…[1618] Multiple classes of sigma-2 ligands have been pharmacologically characterized as either agonists, partial agonists or antagonists. [1921] Sigma-2 agonists have been shown to undergo receptor-mediated endocytosis providing a method to deliver therapeutics into cancer cells.…”
Section: Introductionmentioning
confidence: 99%
“…[1921] Sigma-2 agonists have been shown to undergo receptor-mediated endocytosis providing a method to deliver therapeutics into cancer cells. [1618] Subcellular localization studies have shown sigma-2 agonists are trafficked to the mitochondria, a common site of therapeutic target due to the regulatory processes of cell homeostasis and apoptosis. [22] Sigma-2 agonists are capable of activating caspase 3, 8 and 9 and inducing cell death through multiple pathways, and there are established methods of increasing the potency through conjugation with cytotoxic payloads.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Further interest in the σ 2 receptor has been generated by the evidence that its activation through specific putative σ 2 agents leads to tumor cell death. A few classes of σ 2 ligands endowed with antiproliferative activity have been developed [14] and some encouraging results from in vivo assays are giving impulse to further studies [15][16][17][18]. In our continuous effort to contribute to the σ 2 -receptor research, we conducted several Structure Affinity Relationship studies (SAfiR) on diverse classes of σ receptor ligands [19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%